When is access to health care equal? some public policy issues - Muraleedharan V.R.
The purpose of public policy, both in market and non-market economics has always been to reduce barriers in access to health care. To achieve this purpose, it has to address certain questions: what does equality of access to health care mean? What can be done to promote equality of access, however it may be defined? - Reproduced
Keywords: Public Policy; Health Services